EUTHANASIA DALAM FILM SANCTUM DALAM PERSPEKTIF ETIKA SITUASI - , TRININGSIH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Euthanasia is defined as die quietly without pain. Euthanasia is an act of giving assistance to end the life of someone who suffers unbearable pain and was facing death. Sanctum is a film that tells the story of the cave diving expedition, and in it there are actions performed euthanasia on severely wounded team members to help stop the pain is not unbearable. The act of euthanasia raises ethical issues, so most people reject euthanasia. The problem of euthanasia in the Sanctum can be answered through ethical approach. Ethics is used to analyze the problem in this thesis is euthanasia ethical situation. The purpose of this study is to reveal that the action in the Sanctum euthanasia is morally correct action. This study is library research using the method of data collection through various literature books. Avenues of research in this thesis, among other things: First, the preparatory phase is the collection and classification of data based on conformity with the material object and formal object